Features of high flow access in the elderly. Issue 1 (May 2019) - Kanno, Taro; Kanno, Yutaka; Shiroi, Kazunari; Kobayashi, Nobuhiko; Matsushita, Natsumi; Kamishima, Kasumi; Hashimoto, Koji; Kamijo, Yuji
Introduction: The number of elderly hemodialysis patients continues to grow. The aim of this study was to investigate differences in elderly high flow access patients compared with middle-aged and young patients. Methods: We performed a retrospective study to determine the characteristics of elderly patients (aged >60 years) following blood flow suppression procedures. Preoperative and postoperative data from 177 patients who underwent blood flow suppression procedures and 73 patients who underwent procedures for run-off vein ligation and subcutaneous fixation of the superficial artery were compared. Results: A high proportion of young (aged 20–40 years) and middle-aged (aged 41–60 years) patients met the criteria for blood flow suppression procedures (flow volume 1500 mL/min, flow volume/cardiac output 35%), whereas a high proportion of elderly patients did not. Moreover, heart strain could evidently be caused even with low flow volume. In elderly patients, a tricuspid regurgitation pressure gradient and right heart strain were observed more frequently. Conclusion: Elderly patients who underwent blood flow suppression procedures or subcutaneous fixation of the superficial artery exhibited lower flow volume, and the effects of high flow access in elderly patients depend on the nature of vascular changes. Ultimately, the underlying conditions and hemodynamics of each patient must be determined on an individual basis.